The transcription factor WRKY25 can act as redox switch to drive the expression of WRKY53 during leaf senescence in arabidopsis - Ana Gabriela Andrade Galan; Jasmin Doll; Edda von Roepenack-Lahaye; Natalie Faiss; Ulrike Zentgraf (Scientific Reports)
Abstract Senescence requires high plasticity and, therefore, must be coordinated by a complex regulatory network. Notably, WRKY transcription factors highly impact senescence regulation. WRKYs can form homo- and heterodimers and contain the binding motifs of WRKY factors in their promoters already forming a complex regulatory network between themselves. For the Arabidopsis hub gene WRKY53, WRKY18 acts as a strong negative while WRKY25 serves as strong positive regulator, creating a smaller subnetwork with high complexity, which we analyzed in detail. Activation of WRKY53 expression by WRKY25 is redox sensitive while repression by WRKY18 was not. Deletions and domain-swapping between WRKY18 and WRKY25 revealed that the N-terminal domain of WRKY25 is crucial for its activator effect on WRKY53 expression. Moreover, WRKY25 does not form homodimers but is able to heterodimerize with WRKY18 also requiring its N-terminal domain. The impact on senescence regulation and on WRKY53 expression was validated in planta using transgenic complementation lines of the wrky25 mutant. Modeling WRKY25 in silico indicated a putative covalent lysine-cysteine NOS redox switch. LC–MS analyses suggest that the NOS bridges really exist. We propose that WRKY25 acts as a redox sensor, balancing the expression and interactions of the WRKY53/WRKY25/WRKY18 network to ensure progressive senescence induction.